Electronic, magnetic, and microwave properties of hard/soft nanocomposites based on hexaferrite SrNi0.02Zr0.02Fe11.96O19 with variable spinel phase MFe2O4 (M = Mn, Co, Cu, and Zn). Issue 24 (15th December 2021) - Almessiere, M.A.; Slimani, Y.; Algarou, N.A.; Gondal, M.A.; Wudil, Y.S.; Younas, M.; Auwal, I.A.; Baykal, A.; Manikandan, A.; Zubar, T.I.; Kostishin, V.G.; Trukhanov, A.V.; et al.
Abstract: Hard/soft nanocomposites (NCs) of SrNi0.02 Zr0.02 Fe11.96 O19 (SrNiZr)/MFe2 O4 (M = Mn, Co, Cu, and Zn) were prepared using a one-pot sol-gel auto-combustion technique. All produced samples showed smooth M − H curves and single peaks on the dM/dH against H curves. This indicates that complete exchange-coupled effects between phases were achieved. Furthermore, the squareness ratio SQR=(M r /M s ) was obtained and found to be higher than 0.5 at 300 K. This refers to the occurrence of excellent exchange coupling behavior among the soft and hard ferrites, and their structures consist of a single magnetic domain. The electrodynamic parameters were investigated in the 2–18 GHz frequency band using a coaxial line. The dependences of the real and imaginary parts of μ and ε as a function of frequency were determined from the measured S-parameters. A strong correlation between the chemical composition of the soft magnetic phase and the electrodynamic parameters of the composite was observed. This was analyzed in terms of the atomic weight and configuration of the electronic shells of the A-cation in the soft phase. The electromagnetic absorption (EMA) of the investigated composites was estimated from the reflection losses calculated from μ and ε. The maximal EMA value was observed.